Polycystic Ovary Syndrome (PCOS) as a Risk Factor for Preeclampsia and Cognitive Dysfunction - Ira Febri Yani; Irmiya Rachmiyani; Yudhisman Imran; Triasti Khusfiani; Dina Putri Nasution; Emad Yousif (CoinReads Media Prima, 2026)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age. PCOS is associated with various metabolic disturbances, such as insulin resistance, obesity, dyslipidemia, and chronic inflammation, which may increase the risk of pregnancy complications, such as preeclampsia. In addition to increasing the risk of preeclampsia, PCOS has also been linked to a decline in cognitive function resulting from the effects of hyperandrogenism, insulin resistance, and systemic inflammation on neuronal function. Therefore, PCOS not only increases the risk of developing preeclampsia but may also play an indirect role in cognitive dysfunction. This narrative review discusses the role of PCOS as a risk factor for preeclampsia and cognitive impairment and the interconnected pathophysiological mechanisms linking these conditions.